(untitled) - Ashton, Thomas Southcliffe (Manchester, 1951)
An impressive set of books on the Industrial Revolution, these comprehensive volumes cover the history of steam shipping, iron and steel production, and railroads―three interrelated enterprises that helped shift the Industrial Revolution.
Keywords: Công nghiệp sắt thép và thương mại,Iron industry and trade; Nước Anh,Great Britain